PENGARUH LATIHAN STROKE KE DINDING DAN LATIHAN STROKE BERPASANGAN TERHADAP KETERAMPILAN FOREHAND GROUNDSTROKE PADA PESERTA UKM TENIS LAPANG UNSIL KOTA TASIKMALAYA - Mulya, Gumilar; Agustryani, Resty (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
Forehand Groundstroke in a tennis game is a stroke that aims to defend or attack. To master the Forehand Groundstroke technique, the authors tried two training methods, namely the method of stroke to wall training and pair stroke training. The purpose of this study was: to find out the difference in influence between stroke to wall exercises and paired stroke exercises on Forehand Groundstroke skills in tennis. Referring to the purpose of the study and to prove the hypothesis, the author uses the experimental method. The population consisted of students from the field tennis UKM in UNSIL, Tasikmalaya City, which numbered 27 people. Samples were taken as many as 20 people using random (random) techniques. The research instrument used to obtain the data was Hewitt tennis achievement from Jack E. Hewitt. Based on hypothesis testing, t arithmetic is outside the interval t table, namely t arithmetic <t 0.995 (18) = -4,500 <2,878. So there was no significant difference from the results of the two groups' exercises, namely group A (stroke to wall exercises) and group B (paired stroke exercises). So that stroke-to-wall exercises and paired stroke exercises have the same effect on Forehand Groundstroke skills in tennis games for students in field tennis UKM UNSIL Tasikmalaya. Thus the null hypothesis is accepted, and the alternative hypothesis is rejected. But based on the results of the average increase it is known that group B has a greater increase than group A.